Merevitalisasi Tanaman Obat Keluarga (TOGA) Desa Tanjung Rambutan - Novian Novian; Ahmad Sarijal; Alfi Rahmi Yulianti; Elvita Pratiwi; Fanny Alfrida Oktaviana; Henni Sriwahyuni Pritama Lamban Gaol; Islahul Adila Rahma; Lukman Lukman; Muhammad Reza Firdaus; Putri Zalika Wulandari; Stevanie Aurelia Anata (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Tanjung Rambutan is one of the villages in Kampar sub-district, Kampar district, Riau Province. The village consist of 4 hamlets, 16 neighborhood associations and 8 community associations. Most of the people of Tanjung Rambutan village work as farmers. Thus, many people in Tanjung Rambutan village are familiar with Family Medicinal Plants. In every hamlet, there are already family medicinal plants, but they are not properly managed and cared for. This Family Medicinal Plant needs to be developed because it is not only used as a spice or cooking ingredient but Family Medicinal Plants can be used as an alternative to maintain and care our health naturally.Family medicinal plants have an essential role in maintaining public health naturally. However, in recent years, the use and maintenance of Family Medicinal Plants has experienced challenges, such as the decline of tradisional knowledge, urbanization, and a shift in interest towards modern medicines. Therefore, Riau University KKN students in Tanjung Rambutan Villages revitalizing or improving the management and use of family medicinal plants is essential to ensure the continued use of the family medicinal plants (TOGA).